Cover Image. Issue 5 (27th September 2022) - Abraham, Getachew; Kechero, Yisehak; Andualem, Dereje; Dingamo, Temesgen
Abstract : The cover image is based on the Original Article Indigenous legume fodder trees and shrubs with emphasis on land use and agroecological zones: Identification, diversity, and distribution in semi-humid condition of southern Ethiopia by Getachew Abraham et al., https://doi.org/10.1002/vms3.858 . Image Credit: Getachew Abraham Mihiretu.